Orientações relativas ao aleitamento materno durante o pré-natal: uma revisão integrativa - Luque, Marina Nardino (Universidade do Vale do Rio dos Sinos, 2014)
This is an integrative review aimed to identify and analyze the national scientific production, published between the years 2003 to 2013 about the guidelines provided to pregnant women during prenatal regarding breastfeeding. Data collection was conducted based on LILACS, SciELO and BDENF using descriptors of breastfeeding, prenatal and nursing. It was selected seven articles that met the inclusion criteria for the study. The results show that there are gaps in breastfeeding regarding to prenatal care, suggesting needs of actions in health and new strategies by nursing professionals in order to improve the rates of breastfeeding.
Keywords: Aleitamento materno; Pré-natal; Enfermagem; Breastfeeding; Prenatal; Nursing